Eurasianisme dan Kebijakan Luar Negeri Rusia - Leonard F. Hutabarat (Jurnal Ilmiah Hubungan Internasional, 2017)
Russia’s engagement in Eurasian integration highlights the challenges that Russia faces in Asia. Russia need to re-establish political and economic influence in the region to maintain her eastward-focused integration drive, including building a southeastwards bridge to China and Asia Pacific. In this context, the cooperative nature of Russian policies is the conditio sine qua non for the establishment of the Eurasian Economic Union in 2015. This article examines Russia’s integration policy in relation to Central Asia and beyond, towards Asia as continent. Regional integration is very much a popular idea, with the potential for economic benefits and increased international influence. Significant steps have been taken towards the creation of the Eurasian Economic Union. However, to implement its regional initiatives and to become a more visible player in the regional multilateral institutions, Russia will have to overcome both the domestic and international limitations it faces. Russia’s current alienation from the West and its growing dependency on China may well finally push it into more actively finding better ways of fullfilling this mission.